The Influence of Woven Fabric Craft Business in Improving the Economy and Strengthening the Cultural Spirit of the Sukarara Village Community - Febrianti, Rizka; Abdullah, M. Renaldy; Imron, Imron; Ganis, M Sawal Abdul; Apriyansyah, Roli (Business Management, 2024)
This research aims to understand the development of woven fabric bussines which can play an important role in improving the economy of a village so that it can improve community welfare.this was also expressed by the management of one the wofen fabric shops located in sukarara village called the drama setya group shop and M.Zaenal Rahman as the secretary of Sukarara village said that economic development,especially in Sukarara village in 2023,will increase much more than the previous year.it  is hoped that with this increase sukarara village is ready to become the center for the best-selling woven cloth crafts from local to international levels.Weaving crafts have great potential on realizing NTB as a fashion center.Sukarara village woven cloth crafts are produced and marketed globally.This research uses qualitative research methods.Data collection techniques are carried out by means of interviews and obsarvations.